Stressed State in a Finite Cylinder with a Circular Crack at Non-stationary Torsion - Demydov, O.V.; Popov, V.H. (Проблеми машинобудування, 2018)
This paper considers a solution to an axially symmetric dynamic problem of determining the stress-state in the vicinity of a circular crack in a finite cylinder. The cylinder lower base is rigidly fixed, and the upper one is loaded with time-dependent tangential stresses. In contrast to the traditional analytical methods based on the use of the integralLaplacetransform, the proposed one consists in the difference approximation of only the time derivative. To do this, specially selected unequally spaced nodes and a special representation of the solution in these nodes are used. Such an approach allows the initial problem to be reduced to a sequence of boundary problems for the homogeneous Helmholtz equation. Each such problem is solved by applying the finite Fourier and Hankel integral transforms with their subsequent inversion. As a result, an integral representation was obtained for the angular displacement through an unknown displacement jump in the crack plane. У статті розв’язана вісесиметрична динамічна задача з визначення напруженого стану в околі кругової тріщини в скінченному циліндрі. Нижня основа циліндра жорстко закріплена, а верхня навантажена тангенціальними напруженнями, які залежать від часу. На відміну від традиційних аналітичних методів, що ґрунтуються на використанні інтегрального перетворення Лапласа, запропонований метод полягає в різницевій апроксимації тільки похідної за часом. Для цього використовуються спеціальним чином підібрані нерівновіддалені вузли та спеціальне подання розв’язку в цих вузлах. Такий підхід дозволяє звести вихідну задачу до послідовності крайових задач для однорідного рівняння Гельмгольца. Кожна така задача розв’язується шляхом застосування скінченних інтегральних перетворень Фур'є і Ганкеля з подальшим їх оберненням. В результаті було отримано інтегральне подання для кутового переміщення через невідомий стрибок цього переміщення в площині тріщини. В статье решена осесимметричная динамическая задача по определению напряженного состояния в окрестности круговой трещины в конечном цилиндре. Нижнее основание цилиндра жестко закреплено, а верхнее нагружено тангенциальными напряжениями, которые зависят от времени. В отличие от традиционных аналитических методов, основанных на использовании интегрального преобразования Лапласа, предложенный метод заключается в разностной аппроксимации только производной по времени. Для этого используются специальным образом подобранные неравноотстоящие узлы и специальное представление решения в этих узлах. Такой подход позволяет свести исходную задачу к последовательности граничных задач для однородного уравнения Гельмгольца. Каждая такая задача решается путем применения конечных интегральных преобразований Фурье и Ханкеля, с последующим их обращением. В результате было получено интегральное представление для углового перемещения через неизвестный скачок этого перемещения в плоскости трещины.